2022
DOI: 10.3389/fmed.2022.1028694
|View full text |Cite
|
Sign up to set email alerts
|

Potential biomarkers of atopic dermatitis

Abstract: Atopic dermatitis (AD) is a chronic, recurrent inflammatory skin disease with a wide range of heterogeneity. Accurate biomarkers or predictors are the keys to instructing personalized tailored precise treatment. The development of technology such as transcriptomics, genomics, and proteomics provides novel insights into the possibility to find potential biomarkers. Meanwhile, emerging minimally invasive methods such as tape stripping were used to reveal different profiles of patients’ skin without biopsy. Sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 82 publications
0
29
0
Order By: Relevance
“…Biomarkers obtained from tape stripping or skin biopsies, as well as biomarkers that correlate with AD comorbidities, were investigated. 88 The fact that CLA + T cells are effortlessly extracted from peripheral blood tests puts them under the category of minimally invasive biomarkers, 21 and reinforces their potential as disease biomarkers in AD.…”
Section: Cla + T Cells In the Clinical Context Of The Ad Patientmentioning
confidence: 99%
“…Biomarkers obtained from tape stripping or skin biopsies, as well as biomarkers that correlate with AD comorbidities, were investigated. 88 The fact that CLA + T cells are effortlessly extracted from peripheral blood tests puts them under the category of minimally invasive biomarkers, 21 and reinforces their potential as disease biomarkers in AD.…”
Section: Cla + T Cells In the Clinical Context Of The Ad Patientmentioning
confidence: 99%
“…It is a member of the Th2 chemokine family that is expressed in the thymus and on keratinocytes, T cells, and dendritic cells (Renert-Yuval et al, 2021). In human AD, CCL17/TARC has been used as a reliable biomarker for assessing ADrelated inflammation and for monitoring the severity of AD (Yu & Li, 2022). In veterinary medicine, Maeda et al (2005) demonstrated that TARC may be similarly implicated in the pathogenesis of canine AD.…”
Section: Immune Physiologymentioning
confidence: 99%
“…Biomarkers obtained from tape stripping or skin biopsies, as well as biomarkers that correlate with AD comorbidities, were investigated. 101 The fact that CLA + T cells are effortlessly extracted from peripheral blood tests puts them under the category of minimally invasive biomarkers. 20 Moreover, their ability to predict and monitor therapeutic responses reinforces their potential as cellular peripheral biomarkers in AD.…”
Section: Cla + T Cell Relationship With Ad Biomarkers and Targeted Th...mentioning
confidence: 99%